Blood borne pathogens in the workplace - Safetycare Australia Pty. Ltd. ([Australia] : Safetycare Australia, 1992)
Describes how to prevent and control bloodborne pathogens in correctional facilities. Covers symptoms of bloodborne diseases, universal precautions, personal protective equipment, and response to an incident
VCD format
Keywords: Blood borne pathogens; Occupational disease -- prevention